Transformations of the Islamic Extremism and the Emergence of the “Islamic State” - Sargis Grigoryan (Banber Arevelagitut'yan Instituti)
The Islamic extremism has deep roots in the Middle East. They were especially active towards the end of the 20th century and in the first and second decades of the 21st century. They took on a new nature with the terrorist acts against the US on September 11 in 2001. In the mid-2000s new and dangerous trends of the Islamic extremism became evident in the Middle East, which became visible in Syria with the declaration of the “Islamic State” (IS) in 2014.